1995
DOI: 10.1002/depr.3050030109
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline in the treatment of women with postpartum major depression

Abstract: No consensus has yet been reached as to whether or not postpartum depression (PPD) represents a distinct clinical entity. Despite the increasing evidence that gender differences may exist in antidepressant treatment response, there is an absence of studies in women with postpartum onset of major depression. The aim of this study was to assess the clinical efficacy of the selective serotonin reuptake inhibitor (SSRI), sertraline, in the treatment of women with a major depressive episode (MDE) that occurred with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 22 publications
3
45
1
2
Order By: Relevance
“…The rapid and marked antidepressant response associated with brexanolone administration contrasts with the 4-6 weeks needed (and low remission rates) that have been reported with SSRIs [9] and other antidepressants [10,11] in the management of patients with PPD. The rapid onset of action and duration of effect observed in this study compared to placebo suggested that brexanolone had the potential to address unmet needs in the treatment of patients suffering from PPD.…”
Section: Editorialmentioning
confidence: 81%
See 1 more Smart Citation
“…The rapid and marked antidepressant response associated with brexanolone administration contrasts with the 4-6 weeks needed (and low remission rates) that have been reported with SSRIs [9] and other antidepressants [10,11] in the management of patients with PPD. The rapid onset of action and duration of effect observed in this study compared to placebo suggested that brexanolone had the potential to address unmet needs in the treatment of patients suffering from PPD.…”
Section: Editorialmentioning
confidence: 81%
“…Women with PPD may be more likely to have a response to serotonergic agents, such as selective serotonin-reuptake inhibitors [9] and venlafaxine [10] than to nonserotonergic tricyclic antidepressants [11]. Oestradiol has been evaluated as a treatment for PPD [12].…”
Section: Editorialmentioning
confidence: 99%
“…Odabran je inhibitor ponovnog unosa serotonina sertralin, koji se u literaturi opisuje kao učinkovit i dobro toleriran lijek za poslijeporođajnu depresiju 20 . Kognitivno-bihevioralna terapija provedena je po načelima standardnima za depresivni poremećaj, no uz prilagođavanje posebnim temama i uvjetima poslijeporođajnog razdoblja.…”
Section: Rasprava I Zaključakunclassified
“…17 Less attention has been given to the efficacy of antidepressant medications for postpartum depression. Uncontrolled studies have typically shown improvement in postpartum depressive symptoms after treatment with antidepressants such as sertraline, 18 fluvoxamine, 19 and venlafaxine. 20 However, because depression normally improves over time even without treatment, it is difficult to know whether the improvement in depressive symptoms seen in these studies can be attributed to antidepressant drugs or other factors.…”
Section: Antidepressant Treatmentmentioning
confidence: 99%